The endoparasitic larval stages of Eoxenos laboulbenei: An atypical holometabolan development (Strepsiptera, Mengenillidae) - Tröger, Daniel (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2020)
Endoparasitic larval stages of Eoxenos laboulbenei were documented with different techniques, with a main focus on the male tertiary larva. Two discrete endoparasitic stages occur, the secondary and the tertiary larva. The presence of large compound eyes and externally visible wing buds in the tertiary larva is a unique feature within Holometabola. The brain with large optic lobes is followed by a single postcephalic ganglionic complex. The cephalic musculature is greatly reduced but pharyngeal dilators and muscles associated with the mouth field are present. Postcephalic sclerites are absent except for the pronotum. The segmented legs bear filiform pretarsal claws. The indirect flight muscles fill up a large part of the metathorax. The 10-segmented abdomen lacks appendages. Pleural folds are present on the thorax and abdomen. The digestive tract is characterized by a very short oesophagus. The large midgut and the narrow hindgut are disconnected. Six short Malpighian tubules are present. Large testes fill out almost the entire abdomen. In contrast to the tertiary larva, the muscles of the secondary larva are not fully differentiated. Cephalic appendages are present as bud-shaped anlagen. The legs lack a pretarsal claw. The developmental transformations are outlined and discussed, also with respect to phylogenetic implications.